Attention Deficit Hyperactivity Disorder - A Pre Audit Study of the Pattern of Drug Treatment in a Specialist Community Child and Adolescent Mental Health Service in the UK - Olubokun, Jibowu (International Journal of Criminology and Sociology, 2015)
Attention deficit hyperactivity disorder (ADHD) is a neuro developmental disorder and a common disorder of childhood with functional impairments and a significant personal, family and psychosocial burden. This is a pre audit study of children and young people with ADHD who were referred to the Specialist Community Child and Adolescent Mental Health service in Calderdale, Halifax in East Yorkshire. The main aim of the pre audit study was to determine and study the pattern of drug treatment with psycho stimulant medication in the service as well to study the socio-demographic characteristics of the children and young people referred. This was a cross - sectional study. Twenty cases were randomly selected from the available records and data was extracted directly from the medical records using data sheets designed for the pre-audit study. Males constituted 85% of the study sample and Females 15%. Age group 9-12 constituted 65% of the sample. The modified release preparation of Ritalin was more commonly prescribed than the immediate release preparation. Some practical advantages and limitations of brands are highlighted. The initial findings are useful and would help to modify the data sheet for improved quality and help to set the ‘audit standards’ for the main audit study. This has clinical governance implications in terms of delivering the most expedient quality care in a Child and Adolescent Mental Health Service.